Community-Augmented Meta-Analyses: Toward Cumulative Data Assessment. (November 2014) - Tsuji, Sho; Bergmann, Christina; Cristia, Alejandrina
We present the concept of a community-augmented meta-analysis (CAMA), a simple yet novel tool that significantly facilitates the accumulation and evaluation of previous studies within a specific scientific field. A CAMA is a combination of a meta-analysis and an open repository. Like a meta-analysis, it is centered around a psychologically relevant topic and includes methodological details and standardized effect sizes. As in a repository, data do not remain undisclosed and static after publication but can be used and extended by the research community, as anyone can download all information and can add new data via simple forms. Based on our experiences with building three CAMAs, we illustrate the concept and explain how CAMAs can facilitate improving our research practices via the integration of past research, the accumulation of knowledge, and the documentation of file-drawer studies.